Histological Characteristics, Cell Wall Hydrolytic Enzymes Activity and Candidate Genes Expression Associated with Seed Shattering of Elymus sibiricus Accessions - Zhao, Xuhong; Xie, Wengang; Zhang, Junchao; Zhang, Zongyu; Wang, Yanrong (Frontiers in Plant Science, 2017)
Elymus sibiricus (siberian wildrye) is a perennial, cool-season, self-pollinating, and allotetraploid grass. As an economically important species, it has been widely grown and used for pasture and hay in northern China. Because of serious seed shattering, however, E. sibiricus is difficult to grow for commercial seed production. To better understand the underlying mechanism of seed shattering, we investigated the differences in seed shattering of cultivars and wild accessions in relation to morphological and genetic diversity, histological characteristics, lignin staining, cell wall hydrolytic enzymes activity and candidate genes expressions. We found high level of morphological and genetic diversity among E. sibiricus accessions. In general, cultivars had higher average pedicel breaking tensile strength (BTS) value than wild accessions, of which PI655199 had the highest average BTS value (144.51 gf) and LQ04 had the lowest average BTS value (47.17 gf) during seed development. Seed shattering showed a significant correlation with seed length (SL), awn length (AL) and 1000-seed weight (KW). Seed shattering was caused by degradation of abscission layers that formed at early heading stage, and degradation of abscission layers occurred at 14 days after heading (DAH). Histological analysis of abscission zone showed a smooth fracture surface on the rachilla in high seed shattering genotype, suggesting higher degradation degree of abscission layers. This may resulted from the increased cellulase (CE) and polygalacturonase (PG) activity found in abscission zone at seed physiological maturity. Staining of pedicels of two contrasting genotypes suggested more lignin deposition in low seed shattering genotype may play an role in resistance of seed shattering. Furthermore, candidate genes that involved in cell wall-degrading enzyme and lignin biosynthesis were differentially expressed in abscission zone, indicating the involvement and role in seed shattering. This study provided novel insights into the mechanism of seed shattering in E. sibiricus.